Numerical study of natural convection in partially heated rectangular enclosures filled with nanofluids - Öztop, Hakan Fehmi; Abu-Nada, Eiyad (Elsevier Science Inc, 2008)
Heat transfer and fluid flow due to buoyancy forces in a partially heated enclosure using nanofluids is carried out using different types of nanoparticles. The flush mounted heater is located to the left vertical wall with a finite length. The temperature of the right vertical wall is lower than that of heater while other walls are insulated. The finite volume technique is used to solve the governing equations. Calculations were performed for Rayleigh number (10(3) <= Ra <= 5 x 10(5)), height of heater (0.1 <= h <= 0.75), location of heater (0.25 <= y(p) <= 0.75), aspect ratio (0.5 <= A <= 2) and volume fraction of nanoparticles (0 <= phi <= 0.2). Different types of nanoparticles were tested. An increase in mean Nusselt number was found with the volume fraction of nanoparticles for the whole range of Rayleigh number. Heat transfer also increases with increasing of height of heater. It was found that the heater location affects the flow and temperature fields when using nanofluids. It was found that the heat transfer enhancement, using nanofluids, is more pronounced at low aspect ratio than at high aspect ratio. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Nanofluids; Heat transfer; Natural convection; Enclosure